Reduced immune response to SARS-CoV-2 infection in the elderly after 6 months - Luo, Qin; Song, Qinqin; Li, Yan; Zong, Kexin; Liu, Ti; He, Junming; Mei, Guoyong; Du, Haijun; Xia, Zhiqiang; Liu, Mi; Song, Juan; Gao, Chen; et al. (Frontiers in Immunology, 2025)
ObjectivesTo evaluate the immune persistence and cross-immune response of elderly individuals after Omicron BA.5 infections.MethodThe neutralizing antibodies against WT, BA.5, XBB.1 and EG.5 strains were analyzed. The T/B-cell subsets’ responses were tested through intracellular cytokine staining and flow cytometry.ResultsThe neutralizing antibodies titers against WT and BA.5 strain, remaining high level for at least 6 months, were higher than that of both XBB.1 and EG.5 variants. The neutralizing antibodies of WT, BA.5, XBB.1, and EG.5 strains in the elderly were slightly lower than those in middle-age. The memory B cells decreased rapidly in the elderly, and Tfh, Th17 cells of the elderly continued to increase for only 3 months, while Tfh and Th17 cells increased in the middle-aged for over 6 months. For the elderly, after peptide stimulation, unswitched/switched memory B cells decreased, while double negative B cells displayed higher proliferation. The proportions of both naïve and Temra cells in CD4+ and CD8+ T cells declined, whereas those of Tcm and Tem cells elevated. In the meantime, both CD69+ and CD38+ T cells decreased, but the frequencies of PD-1+ and CTLA-4+ of CD4+ and CD8+ T cells showed an increasing trend. The proportions of PD-1+ and CTLA-4+ cells also increased in older people with long COVID symptoms at 3m post-infection.ConclusionsOmicron BA.5 infection induced lower neutralizing antibodies against XBB.1 and EG.5 variant. The decrease of memory B cells, CD69+ and CD38+T cells, as well as the increase of PD-1+, CTLA-4+ of CD4+/CD8+T cells and double negative B cells, indicate that sustained immune responses against BA.5 infection may wane more rapidly in elderly populations.